First report on seroepidemiology of Toxoplasma gondii infection in pigs in Central Ethiopia - Gebremedhin, Endrias Zewdu (BMC Vet Res, 2015)
BACKGROUND: Toxoplasma gondii is one of the most widely prevalent cyst forming Apicomplexan parasites with significant impact on animal production particularly in sheep, goats and pigs. The objectives of this cross-sectional study were to estimate the seroprevalence and to assess risk factors of Toxoplasma gondii infection in pigs. A systematic random sampling technique was used to collect 402 blood samples from pigs in Central Ethiopia. Direct Agglutination Test (DAT) was used to test sera. A questionnaire survey was made to assess potential risk factors and knowledge of farm attendants about toxoplasmosis. RESULTS: An overall seroprevalence of 32.1% [95% confidence interval (CI): 27.6%-36.9%] was found. Multivariable logistic regression analysis showed that extensively managed pigs (39.7%) are nearly twice (adjusted odds ratio [aOR]:=1.91, 95% CI: 1.01, 3.63) at higher risk of acquiring toxoplasmosis than intensively managed pigs (30.5%). Pigs supplied with feed containing animal byproducts had nearly four times (OR = 3.84, 95% CI: 2.01, 7.36) higher risk of acquiring T. gondii infection. Most of the farm attendants had little knowledge of health risks due to cats, neither to human nor to animals. Absence of rodent control, high neonatal mortality and history of abortion were found among herds of the studied pig farms. CONCLUSIONS: T. gondii infections in pigs are wide spread. Extensive management systems and pig feed types containing animal byproducts are independent predictors of T. gondii seropositivity. The high seroprevalence suggests that pigs might serve as an important source of T. gondii infection for people. This is the first report of seroepidemiology of T. gondii infection in pigs in Ethiopia. Further studies are warranted for designing appropriate prevention and control strategies.